E. coli Sepsis: Red Flag for Colon Carcinoma—A Case Report and Review of the Literature - Hiren G. Patel; Seme Tabassum; Sohail Shaikh (Case Reports in Gastrointestinal Medicine)
We present an atypical case of newly diagnosed colon cancer and provide insight into the infectious predispositions of E. coli bacteremia to the development of colon adenocarcinoma. A 66-year-old female was admitted to the hospital with one-week symptoms of subjective fevers, chills, and lower back pain. Upon initial evaluation, her temperature was 101 degrees Fahrenheit with a white count of 12,000 K/mm3. Initial septic workup was positive for E. coli bacteremia. The patient was started on Aztreonam. Repeat blood culture 48 hours later was negative for any growth. However, later during hospital stay blood culture was repeated due to SIRS, which was positive again for E. coli. CT scan of the chest/abdomen/pelvis with contrast revealed no signs of colitis. Without clear etiology for recurrent E. coli bacteremia ultimately colonoscopy was performed which showed an ulcerated mass in the cecum. Biopsy showed moderately differentiated adenocarcinoma. E. coli strains B2 and D produce cyclomodulin toxins as part of their virulence, which interferes with the cell cycle regulation, promoting chromosomal instability, and increasing susceptibility to cancer. In patients with recurrent E. coli bacteremia with an unknown source, colonoscopy should be done to look for colon cancer.